2001
DOI: 10.1890/1051-0761(2001)011[1722:ipfpct]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Process From Pattern: Can Territory Occupancy Provide Information About Life History Parameters?

Abstract: Abstract. A significant problem in wildlife management is identifying ''good'' habitat for species within the short time frames demanded by policy makers. Statistical models of the response of species presence/absence to predictor variables are one solution, widely known as habitat modeling. We use a ''virtual ecologist'' to test logistic regression as a means of developing habitat models within a spatially explicit, individual-based simulation that allows habitat quality to influence either fecundity or survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(38 citation statements)
references
References 72 publications
(80 reference statements)
0
38
0
Order By: Relevance
“…Accurate distribution maps of organisms are welcomed in the selection and design of natural parks (Scott et al, 1993), the assessment of human impacts on biodiversity (Lavers and Haines-Young, 1996), or the testing of biogeographical hypotheses (Mourell and Ezcurra, 1996;Leathwick, 1998). However, even a perfect knowledge of the biology of a species cannot guarantee that a static map will reflect dynamic properties of species distribution (Tyre et al, 2001). Moreover, human and logistic limitations make it impractical to survey large areas and, inevitably, our knowledge of the spatial distribution of most species will have many gaps (Osborne and Tigar, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate distribution maps of organisms are welcomed in the selection and design of natural parks (Scott et al, 1993), the assessment of human impacts on biodiversity (Lavers and Haines-Young, 1996), or the testing of biogeographical hypotheses (Mourell and Ezcurra, 1996;Leathwick, 1998). However, even a perfect knowledge of the biology of a species cannot guarantee that a static map will reflect dynamic properties of species distribution (Tyre et al, 2001). Moreover, human and logistic limitations make it impractical to survey large areas and, inevitably, our knowledge of the spatial distribution of most species will have many gaps (Osborne and Tigar, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, human and logistic limitations make it impractical to survey large areas and, inevitably, our knowledge of the spatial distribution of most species will have many gaps (Osborne and Tigar, 1992). A common solution to this problem is to resort to predictive habitat modelling (reviewed in Guisan and Zimmermann, 2000, and see some recent examples in Osborne et al, 2001;Scott et al, 2002;Seoane et al, 2003) and regard the results as potential habitat, able to be reached and colonised by a species (Tyre et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has to be considered that demographic stochasticity and dispersal can prevent a perfect adjustment between predictive models and wildlife distribution as Tyre et al (2001) have shown with computer simulation models. Also, it is interesting to note that when general-purpose land-use/land-cover maps of enough accuracy and resolution are not available there is the alternative of deriving vegetation structural characteristics from satellite images resulting in maps with similar predictive ability of bird distribution.…”
Section: Discussionmentioning
confidence: 99%
“…an species has not occupied all potential adequate habitat because of geographical barriers, or because it has been extirpated by man from otherwise suitable habitat). (c) Unsaturated habitats (small populations are not able to occupy all suitable habitats, but also demographic stochasticity and localised dispersal generate an imperfect correlation between habitat suitability and species distribution; Tyre et al, 2001). (d) Poor quality of the response variable (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, HSMs based on land use, topographic and climatic predictors may sometimes show large difference between predicted and observed values (Massimino 2004). This can be due to inadequacy of the modelling technique, unsaturated habitats (Cardillo et al 1999;Tyre et al 2001) or failure to include significant environmental predictors (Crawley 1993;Guisan & Thuiller 2005), whose selection is often critical and strongly dependent on the type of selection strategy used (Ara煤 jo . Moreover, occurrence of many species can be influenced by environmental characteristics or processes that are difficult to measure, or at least have not been measured adequately.…”
Section: Introductionmentioning
confidence: 99%